The Cultivation of Civil Values through Thematic-Based Science Practices in Low Grade Elementary Schools - Supriyanto, Djoko Hari; Haryanto, H (Proceedings International Conference on Education Innovation and Social Science, 2023)
Learning is a conscious effort to get change behavior overall, both aspects cognitive, affective and psychomotor. So far in in practice, the learning process at school it seems more likely to emphasize on achievement aspect changes cognitive. Whereas affective abilities are still lacking attention. In learning, affective abilities relate to ethical values. The values of character must be instilled and received serious concern from parties involved in education. Science lessons, which so far have been considered far from affective aspects, can also be used to instill moral values, namely by carrying out practicums. The science practicum applied so far is more likely to be carried out with a conceptual approach, so that if applied it will make learning fragmented. While students who are at elementary school low class still see everything as one wholeness (holistic) so that thematic learning is used in the lower grades of elementary school. For this reason, a design for science practicum in low grade elementary schools is needed which can be applied through thematic learning. From the description above so the purpose of this research is to know practical application of IPA based thematically to embed moral values to low grade elementary school students. This activity is carried out January to March 2023 at Tambakromo 2 public elementary school, Padas District, Ngawi Regency. The subjects in this study were all class students, totaling 24 students. Data collection was carried out by observation and test techniques. which method used in this research is Classroom Action Research or Action Research Class with two cycles. From the implementation of cycle I activities and II it can be seen that an increase in cognitive and psychomotor values. The affective ability of students also increased, which was marked by an increase in the percentage for good and very good criteria. Meanwhile, for the criteria of sufficient, less, and bad, there was a decrease. This increase in students' affective abilities also shows an increase in students' moral values. From research implementation class action It can be concluded that the application of thematic-based science practicum is able to instill values manners on elementary school students low class.